2018
DOI: 10.1093/mnras/sty226
|View full text |Cite
|
Sign up to set email alerts
|

The star formation history of the Sextans dwarf spheroidal galaxy: a true fossil of the pre-reionization era

Abstract: We present the star formation history (SFH) of the Sextans dwarf spheroidal galaxy based on deep archive B,I photometry taken with Suprime-Cam at Subaru telescope focusing our analysis on the inner region of the galaxy, fully located within the core radius. Within the errors of our SFH we have not detected any metallicity gradient along the considered radial distance interval. As a main result of this work we can state that the Sextans dwarf spheroidal stopped forming stars less than ∼ 1.3 Gyr after Big Bang i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 59 publications
3
36
1
Order By: Relevance
“…The lack of metals before the onset of type Ia SNe in Sextans could be also explained by a short main episode of star formation. Bettinelli et al (2018) found that the main episode of star formation lasted only ∼0.6 Gyr and ended ∼12.9 Gyr ago, which supports the hypothesis that Sextans quickly drained most of its gas reservoir.…”
Section: The Imf and The Alpha Kneesupporting
confidence: 74%
“…The lack of metals before the onset of type Ia SNe in Sextans could be also explained by a short main episode of star formation. Bettinelli et al (2018) found that the main episode of star formation lasted only ∼0.6 Gyr and ended ∼12.9 Gyr ago, which supports the hypothesis that Sextans quickly drained most of its gas reservoir.…”
Section: The Imf and The Alpha Kneesupporting
confidence: 74%
“…For our comparison with observations we use the results of Leaman et al (2013) and Kacharov et al (2017) to compile stellar metallicity gradient information for a total of 10 Local Group dwarfs. We then use t 50 values determined from the star formation histories created in Weisz et al (2014a,b), and Bettinelli et al (2018). Table 2 summarises the t 50 values, gradient strengths, γ z , and the effective radii taken from McConnachie (2012), Munoz et al (2018), andSimon (2019) -for the ten galaxies we analyse.…”
Section: Observational Comparisonmentioning
confidence: 99%
“…Properties of 10 observed Local Group galaxies: (1) lookback time to the formation of 50% of stars determined from published SFHs(Weisz et al 2014a,b;Bettinelli et al …”
mentioning
confidence: 99%
“…Altogether, observations of the known UFD population orbiting the Milky Way suggest that these very low-mass systems have old stellar populations, with little star-formation activity since z ∼ 1−2 (e.g. Okamoto et al 2008Okamoto et al , 2012de Jong et al 2008;Sand et al 2009Sand et al , 2010Sand et al , 2012Brown et al 2012;Martin et al 2015;Bettinelli et al 2018).…”
Section: Ufd Galaxy Samplementioning
confidence: 99%